SUBSTITUSI TEPUNG KULIT MANGGIS DALAM PEMBUATAN STIK BAWANG - Gunawan, Agung Arif; Ridwan, Zahra Ananda (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2024)
Mangosteen production in Indonesian to increase excessive production will have an impact on the environment, especially as a result of post-mangosteen skin consumption. Mangosteen peel is still seen as waste because it has not been utilized optimally.Mangosteen peel flour is flour derived from the destruction of mangosteen peel that has been dried and then crushed and sifted. By using mangosteen peel waste that has been made into flour as a substitution or addition to the onion stick will increase the nutritional content of the onion stick. In optimizing mangosteen peel waste which reaches 50% of the weight of the fruit, the author conducted research to reduce mangosteen peel waste to be used as a utilization of one of them as mangosteen peel flour.Onion sticks are snacks made from wheat flour that has a distinctive taste and aroma of onions produced from adding onions to onion stick dough, this snack is very popular among the surrounding community. This is the background for the author to take the onion stick object as an experimental project.This research uses organoleptic tests, namely hedonic quality tests and hedonic tests with the hypothesis results stating that there are differences in taste, color, texture and aroma.